Aggregation‐Induced Absorption Enhancement for Deep Near‐Infrared II Photoacoustic Imaging of Brain Gliomas In Vivo. Issue 8 (16th January 2019) - Liu, Yajing; Liu, Huanhuan; Yan, Huixiang; Liu, Yingchao; Zhang, Jinsen; Shan, Wenjun; Lai, Puxiang; Li, Honghui; Ren, Lei; Li, Zijing; Nie, Liming
Abstract: The delineation of brain gliomas margins still poses challenges to precise imaging and targeted therapy, mainly due to strong light attenuation of the skull and high background interference. With deep penetration and high sensitivity, photoacoustic (PA) imaging (PAI) in the second near‐infrared (NIR II) window holds great potential for brain gliomas imaging. Herein, mesoionic dye A1094 encapsulated in Arg‐Gly‐Asp‐modified hepatitis B virus core protein (RGD‐HBc) is designed and synthesized for effective NIR II PAI of brain gliomas. An aggregation‐induced absorption enhancement mechanism is discovered in vitro and in vivo. It is also demonstrated that A1094@RGD‐HBc, with an enhanced absorption in the NIR II window, displays ninefold PA signal amplification in vivo, allowing for precise PAI of the brain gliomas at a depth up to 5.9 mm. In addition, with the application of abovementioned agent, high‐resolution PAI and ultrasensitive single photon emission computed tomography images of brain gliomas are acquired with accurate co‐localization. Collectively, the results suggest great promise of A1094@RGD‐HBc for diagnostic imaging and precise delineation of brain gliomas in clinical applications. Abstract : Here, an aggregation‐induced absorption enhancement mechanism and application of A1094 aggregates for brain gliomas imaging are presented.